Dimensions of Resilience Among Women with Autoimmune Conditions: A Qualitative Study in Tehran - Mahmoodzadeh, Sepideh; Ghezelseflo, Mehdi; Rahsepar Monfared, Farnaz (Journal of Personality and Psychosomatic Research (JPPR), 2025)
This study aimed to explore and conceptualize the multidimensional nature of resilience among women living with autoimmune conditions, focusing on their cognitive, emotional, social, and spiritual adaptation processes. A qualitative phenomenological design was employed to gain a deep understanding of women’s lived experiences of resilience while coping with autoimmune diseases. Using purposive sampling, twenty-one women diagnosed with autoimmune conditions—including lupus, rheumatoid arthritis, multiple sclerosis, and thyroid disorders—were recruited from medical centers in Tehran. Data were collected through semi-structured, in-depth interviews lasting 45–75 minutes. Interviews were recorded, transcribed verbatim, and analyzed thematically using Braun and Clarke’s (2006) framework with the assistance of NVivo 14 software. Data collection continued until theoretical saturation was reached. Trustworthiness was ensured through member checking, peer debriefing, and maintaining an audit trail. Thematic analysis revealed four overarching dimensions of resilience: (1) Cognitive Adaptation—involving reframing illness, future orientation, and meaning-making through knowledge; (2) Emotional Regulation—including acceptance, emotional endurance, and positive emotional expression; (3) Social Connectedness—encompassing family support, peer empathy, and identity reconstruction through relationships; and (4) Spiritual and Existential Resilience—defined by faith, gratitude, moral integrity, and spiritual integration with medical care. Resilience among women with autoimmune diseases emerges as a multifaceted and culturally embedded phenomenon, rooted in cognitive flexibility, emotional mastery, social solidarity, and spiritual meaning-making. Interventions should therefore adopt holistic and culturally sensitive approaches that address both psychosocial and existential needs, empowering women to live purposefully despite chronic adversity.